2016
DOI: 10.1155/2016/6896024
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Biomarkers in Colorectal Cancer: From the Single Therapeutic Target to a Plethora of Options

Abstract: Colorectal cancer (CRC) is one of the most frequent cancers and is a leading cause of cancer death worldwide. Treatments used for CRC may include some combination of surgery, radiation therapy, chemotherapy, and targeted therapy. The current standard drugs used in chemotherapy are 5-fluorouracil and leucovorin in combination with irinotecan and/or oxaliplatin. Most recently, biologic agents have been proven to have therapeutic benefits in metastatic CRC alone or in association with standard chemotherapy. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…It was recently announced that the drugs with certain mechanisms of action are targeted by molecules in tumors and are not so effective for common cancers. It was also announced that approaching a single target cannot inhibit the tumor progression in multisystem involving cancers such as colorectal cancer [ 12 ]. By analyzing these study results, it is shown that the failure or less effect of drugs may be caused by interaction of many signal pathways.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently announced that the drugs with certain mechanisms of action are targeted by molecules in tumors and are not so effective for common cancers. It was also announced that approaching a single target cannot inhibit the tumor progression in multisystem involving cancers such as colorectal cancer [ 12 ]. By analyzing these study results, it is shown that the failure or less effect of drugs may be caused by interaction of many signal pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Colorectal cancer develops from the progressive accumulation of molecular events, like somatic mutations in oncogenes, or epigenetic mechanisms such as methylation of DNA or post-transcriptional modification of histones 2 . Over recent years, various studies have focused on the discovery of the molecular changes that participate in the process of tumour development, with the aim of finding biomarkers potentially useful in predicting survival or directing therapeutic strategies 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The significance of (KRAS) Kirsten rat sarcoma viral oncogene homolog mutational profile as a negative predictive biomarker in the treatment response of mCRC using monoclonal antibody (mAb) against epidermal growth factor receptor (EGFR) is well established [55][56][57]. Clinical trials such as PRIME (panitumumab) and CRYSTAL (cetuximab) demonstrated positive response towards anti-EGFR mAb therapies only in wild-type (WT) KRAS mCRC patients.…”
Section: Kras (Kirsten Rat Sarcoma Viral Oncogene Homolog)mentioning
confidence: 99%
“…Significant correlations with known CRC biomarkers such as MSI-H, KRAS, and BRAF mutations were also reported [100]. A simplified summary of the biomarkers reviewed in Section 2.1 to 2.4 is presented in Figure 2 [18,19,43,54,56,57,70,74,78,79,88,[91][92][93][94]96,97,[100][101][102][103][104][105].…”
Section: Consensus Molecular Subtypes (Cms)mentioning
confidence: 99%